2012
DOI: 10.1080/09540121.2012.748881
|View full text |Cite
|
Sign up to set email alerts
|

Do HIV-positive adult immigrants need to be screened for measles–mumps–rubella and varicella zoster virus immunization?

Abstract: A systematic screening for measles, mumps, rubella (MMR) and varicella zoster virus (VZV) in HIV-positive adult immigrants in Spain was evaluated, and factors associated with MMR and VZV vaccines' indication were studied. Every HIV-positive immigrant was tested for VZV and MMR-IgG. MMR vaccine was indicated to patients with lymphocytes CD4+ >200 cells/mm³ and a negative measles-IgG, a negative mumps-IgG and/or a negative rubella-IgG. VZV vaccine was indicated to every VZV-IgG negative patient with CD4+ >400 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
3
7
1
Order By: Relevance
“…In patients born outside of France (36.2%), the prevalence of measles seronegativity did not differ from that of patients born in France. This result is consistent with the prevalence of measles seronegativity (4.9%) observed in HIV adult immigrants in Spain in 2008-2009 [5]. In line with our study, age less than 30 years was a significant risk factor for measles seronegativity (11% versus 2.5%; P ¼ 0.01) [5].…”
supporting
confidence: 95%
“…In patients born outside of France (36.2%), the prevalence of measles seronegativity did not differ from that of patients born in France. This result is consistent with the prevalence of measles seronegativity (4.9%) observed in HIV adult immigrants in Spain in 2008-2009 [5]. In line with our study, age less than 30 years was a significant risk factor for measles seronegativity (11% versus 2.5%; P ¼ 0.01) [5].…”
supporting
confidence: 95%
“…Thus, the likelihood of HIV-positive individuals being in contact with vaccine-preventable infections in occupational, social and travel exposures has increased substantially. At the same time, studies from other countries have demonstrated low frequency of seropositivity against MMR or VZV in HIV-positive patients, especially in young adults [1,[8][9][10][11][12][13]. The guidelines from the European AIDS Clinical Society (EACS) therefore recommend a proactive approach towards screening and vaccination in HIV-positive individuals [14].…”
Section: Introductionmentioning
confidence: 99%
“…Being born after 1970 was the second risk factor independently associated with measles seronegativity in the present study. Younger age as a risk factor for measles seronegativity in HIV‐infected subjects has been reported in other recent studies in France, Spain and Germany . In Belgium, the measles vaccine has been available since 1974 and MMR vaccination with one dose was introduced to the childhood routine schedule in 1985, while two doses were implemented in 1995 .…”
Section: Discussionmentioning
confidence: 62%